Study of the chemical composition of dichloromethane extract Tamarix hispida - Ikhsanov, Y.S.; Abilov, Zh.A.; Choudhary, M.I.; Sultanova, N.A. (KSU Publ., 2018)
In this article, first time there was observed dichloromethane extract from the aerial part of the Tamarix hispida (Tamaricaceae) harvested in the Almaty region of the Republic of Kazakhstan. The extraction of the previously dried and crushed vegetable raw material was carried out with dichloromethane in a Soxhlet apparatus. The extract was investigated by gas chromatography with mass spectrometry module under the following conditions: SHP-5MS gas chromatography column (30 m × 250 mm × 0.25 mm) temperature at 40 ºC for 5 minutes. As the carrier gas we used helium at a flow rate of 1 ml/min; with temperature programming up to 250 ºC and a temperature change of 50 ºC/min. Sample 0,2 μl was taken for assay. The compounds were identified by mass spectra and retention times, using the NIST library and Wiley GC/MS. As a result 25 compounds were identified in the dichloromethane extract which the highest contents were: picheol; methyl 3-(acetoxy)-20-hydroxy-12-en-28-oate; 6,10,14-trimethyl-2-pentadecanone; 2-hydroxy-1,1,10-trimethyl-6,9- epidioxydecalin, respectively. The presence of halogen-organic compounds: heptadecyl ester of 3-chloropropionic acid, 2-chlorophenylethyl ester of fumaric acid and 1,54-dibromo tetrapentacontane were detected in the extract. Halogen-containing compounds were firstly detected in the genus Tamarix.
Tamarix hispida өсімдігінің дихлорметандық экстрактының химиялық құрамы
Исследование химического состава дихлорметанового экстракта Tamarix hispida
Keywords: dichloromethane extract; Tamaricaceae; Tamarix hispida; aerial mass; halogenorganic compounds; dichloromethane; chromatography-mass spectrometry; Soxhlet method